Exploring the Negative Impacts of Students' Dependence on AI Technology Based on Digital Literacy in Arabic Language Materials - Hakim Mustofa, Muhammad; Dwi Mayasari, Utari; Muhyidin; Abdullah, Ahmad Hafidz (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
This research explores the negative impact of students' dependency on AI technology based on digital literacy in the 5.0 era, with an additional focus on integrating Arabic language learning. Students overly reliant on technology tend to experience a decline in creativity, integrity, and their role as agents of change. The study aims to analyze the negative values associated with technological advancements, comprehend the root causes, and enhance awareness to reduce students' dependence on AI technology. Data collection utilizes documentation study or literature review techniques. Findings indicate the significance of education and the educator's role in shaping ethical awareness of AI technology usage, involving social media and online platforms. The research emphasizes the need for collaborative efforts to raise awareness and diminish students' dependency on AI technology, involving educational institutions, educators, society, and incorporating Arabic language learning material holistically.